Q: What is 6x plus 9 plus 5x minus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7-5x=10-(6x+7) 7-5x=-60x-70 +5x +5x 7=-55x-70 +70 +70 77=-55x Divide -55 -1.4 = x

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11

you say: 5x+7=84-6x 5x+6x+7=84-6x+6x 11x+7=84 11x+7-7=84-7 11x=77 x=77/11 x=7

11x-7

2x + 7 + 5x - 4 - x = (2x + 5x - x) + (7 - 4) = 6x + 3

Related questions

x = 0,1

-6x+3 = -7-5x 7+3 = 6x-5x 10=x

7-5x=10-(6x+7) 7-5x=-60x-70 +5x +5x 7=-55x-70 +70 +70 77=-55x Divide -55 -1.4 = x

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11

you say: 5x+7=84-6x 5x+6x+7=84-6x+6x 11x+7=84 11x+7-7=84-7 11x=77 x=77/11 x=7

11x-7

2x + 7 + 5x - 4 - x = (2x + 5x - x) + (7 - 4) = 6x + 3

It is: 42x+30x^2

4

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

(x - 1)(5x + 7)

5x+3x-6x+4x+2x-x+10 This expression can be simplified to: 7x+10 (7 being the coefficient of x)